Pengaruh Pendidikan dan Pelatihan (Diklat) terhadap Kinerja Karyawan pada PT. Tehnik Bayu Murni, Jakarta - Refi, Muhamad Zaenul; Amin, Mustangin (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Employee performance plays a crucial role in determining organizational success, particularly in highly competitive industries such as machinery and shipping. However, preliminary observations at PT. Tehnik Bayu Murni Jakarta indicate suboptimal employee performance, reflected in high absenteeism, low work discipline, and delays in task completion. This study aims to examine the effect of education and training (Diklat) on employee performance. A quantitative research method was employed using a simple random sampling technique involving 50 operational employees. Data were collected through structured questionnaires and analyzed using simple linear regression, Pearson correlation, and coefficient of determination with SPSS version 25. The validity and reliability tests confirmed the quality of the instrument. The results reveal a significant and positive influence of education and training on employee performance, as shown by a t-value of 5.944 (t-table = 1.677; p < 0.05) and a Pearson correlation coefficient of 0.651. The coefficient of determination (R²) indicates that 42.4% of the variation in employee performance can be explained by the training variable. These findings highlight the strategic importance of structured and relevant training programs in enhancing employee competence and organizational productivity. It is recommended that the company improve the relevance and delivery of training materials and regularly evaluate training outcomes to ensure sustainable performance improvements.